2014
DOI: 10.1007/s00216-014-7644-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of pesticides not amenable to multi-residue methods by flow injection–tandem mass spectrometry

Abstract: Flow injection combined with tandem mass spectrometry (MS/MS) was investigated for the rapid detection of highly polar pesticides that are not amenable to multi-residue methods because they do not partition into organic solvents and require dedicated chromatographic conditions. The pesticides included in this study were amitrole, chlormequat, cyromazine, daminozide, diquat, ethephon, fosetyl-Al, glufosinate, glyphosate and its metabolite aminomethylphosphonic acid, maleic hydrazide, mepiquat and paraquat. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…According to Mol et al, () the sensitivity of the FIA method is strongly dependent on the analyte's peak shape, which in turn depends on the capillary internal diameter, length, and the flow rate of the solvent. In this work, the highest sensitivity was achieved with the 0.13 mm internal diameter capillary of ~1 m length between the autosampler and the ionization source of the mass spectrometer, flow solvent delivery rate was set at 350 μL/min.…”
Section: Resultsmentioning
confidence: 99%
“…According to Mol et al, () the sensitivity of the FIA method is strongly dependent on the analyte's peak shape, which in turn depends on the capillary internal diameter, length, and the flow rate of the solvent. In this work, the highest sensitivity was achieved with the 0.13 mm internal diameter capillary of ~1 m length between the autosampler and the ionization source of the mass spectrometer, flow solvent delivery rate was set at 350 μL/min.…”
Section: Resultsmentioning
confidence: 99%
“…As for LOD, other authors found, in food matrices [ 18 ], comparable values (0.2 mg·kg −1 ) of fosetyl. In air particulate matter (PM 2.5 ), Coscollà et al [ 19 ] found, for other pesticides by LC-MS/MS, LOQ values with the same order of magnitude (pg·m −3 ).…”
Section: Resultsmentioning
confidence: 75%
“…The following parameters were considered: (i) sample loop volume, (ii) composition of carrier solution, (iii) flow rate and (iv) sampling frequency. As recommended elsewhere , capillary PEEK tubing with internal diameter of 0.005″ was applied for connecting a Rheodyne injection valve with the ESI and the shortest possible distance was set (9 cm). The sample loop was made from this same tube, 2 μL volume was sufficient for the acquisition of mass spectrum and for signal integration, and provided the fit‐for‐purpose sensitivity.…”
Section: Resultsmentioning
confidence: 99%